Protótipo de sistema para coleta de dados inerciais com foco na doença de Parkinson - Martins, Wanghley; Oliveira, Fábio Henrique (Anais do Encontro Nacional de Computação dos Institutos Federais (ENCompIF), 2020)
Currently, the diagnosis and monitoring of people affected by neurodegenerative diseases are made subjectively. Parkinson's disease (PD), for example, is a neurodegenerative disease that affects the motor part of the individual. The evaluation of PD usually is done through scales based on questionnaires. Thus, this research is dedicated to the study and development of a computational system capable of performing the collection, transmission and visual presentation of data related to the human movement, in order to assist the diagnosis and monitoring of PD.